ANALYSIS OF IMPLEMENTATION IN DAY CARE BASED INTEGRATIVE HOLISTICS IN DIVISION B PT ASAM JAVA – TORGAMBA - Sitepu, Juli Maini; Sari, Fatimah (Proceeding International Seminar of Islamic Studies, 2024)
Integrative holistic program is one of the treatment programs child age early in a way intact or comprehensive covering _ service nutrition and health , education and care as well as protection For optimizing all aspect development child age early . Study This aim For know is activity holistic integrative based can implemented with both at the PT Asam Jawa Torgamba Division B Child Care Center . As for methods research used _ is method Interpretative with source of data obtained through observation , interviews and documentation to educators / caregivers and TPA leaders . Research result show that activity based holistic integrative Already held through activity play good inside _ or outside _ room , and existence habituation For stimulating all over aspect development the child did in a way systematic in accordance existing schedule _ determined previously .